(3GdJMdjd GdeGdj h GdGbJUGOj (B:s (3aj OQGSGJ Jbjje h LOhi GdeTGQjY (B/s - (3GdTeQj, NGdO Jhajbs ((3YeGf(B: s (3OGQ hGFd(B, s, 2010)
(3fWGb OQGSGJ GdLOhi GdGbJUGOjI , GdJMdjd GdeGdj , OQGSI GdLOhi GdafjI , , GdJbjje GdGbJUGOj h GdGLJeGYj h bjGS GdQHMjI GdbhejI , MGdGJ YedjI dOQGSGJ GdLOhi (B.s
(3eQGLY U(B.277 (3; edGMb U(B.233s
Keywords: (3EOGQI GdeTGQjYs; (3GdJMdjd GdGbJUGOjs; (3GdJMdjd GdeGdjs; (3GdLOhi GdGbJUGOjIs; (3GdeTGQjYs